In Vitro Removal of T‐2 Toxin by Yeasts. Issue 4 (2nd June 2015) - Zou, Zhongyi; Sun, Jianli; Huang, Fei; Feng, Zhi; Li, Minji; Shi, Ruiting; Ding, Junxia; Li, Hongjun
Abstract Five yeast strains were tested for their ability to remove T‐2 toxin from yeast extract peptone dextrose medium. The ability of Saccharomyces cerevisiae 1221 (SC1221) was the strongest among five strains, and 36.50 ± 1.40% of T‐2 toxin was removed after incubation at 30C for 96 h. The mode of removal was physical binding rather than biotransformation. The total amount of T‐2 toxin released from viable Saccharomyces cerevisiae 1221 cell–toxin complexes was 37.39 ± 0.48% of total bound T‐2 toxin, respectively, after three times of washing with phosphate buffered saline, which was 8.17 ± 0.75% after incubation with simulated gastric fluid at 37C for 4 h, and which was 13.22 ± 0.61% after incubation with simulated intestinal fluid at 37C for 4 h, respectively. Practical Applications T‐2 toxin is the most toxic trichothecene, which is commonly found in cereal grains, animal feed and human food produced from contaminated grains. The best solution for decontamination should be detoxification by microorganisms, giving a possibility for removal of mycotoxins under mild conditions, without using harmful chemicals and significant losses in nutritive value and palatability of decontaminated food and feed. Yeasts have immense potential as tools in tackling the problem of mycotoxins in cereal‐based foods and in animal feeds. The objective of this work was to investigate the effect of food‐grade yeast strains on the removal of T‐2 toxin in vitro. Results of this study indicated that the strain of Saccharomyces cerevisiae 1221 (SC1221) has a strong ability to remove T‐2 toxin. Therefore, this strain could be potentially applied in food and feed industry for detoxification of T‐2 toxin.